(untitled) (Bangladesh Journal of Medical Education, 2024)
Background: The internet is essential for social interaction, information acquisition, and entertainment. The internet has a vast amount of knowledge that is accessible with only a click. For a student of today, it is horrifying to consider academic or research activity without internet. However, the indiscriminate use of the internet by individuals, especially students, may hamper their academic performance and quality of life. This study aimed to measure the extent of internet use among undergraduate medical students. Methods: This cross-sectional study was performed among 926 undergraduate medical students and interns from nine medical colleges of Bangladesh, who were selected using the convenience sampling method. The extent of internet use was assessed by the duration of internet use for academic and non-academic purposes, as well as the Internet Addiction Test (IAT) developed by Kimberly Young. Results: This study revealed that the mean (SD) hours of internet use for academic purposes, non-academic purposes and total duration of internet use were 2.34 (±1.991), 3.74 (±2.413) and 6.08 (±3.124 respectively. Additionally, 39.3%, 33%, and 2.3% of students had mild, moderate, and severe levels of internet addiction, respectively. Conclusion: The results of this study indicate that a substantial proportion of undergraduate medical students are spending a considerable amount of time on the internet, with a majority using it for more than 3 hours per day on average. Moreover, a significant portion of these students demonstrated varying levels of internet addiction. BJME, Volume-15, Issue-01, January 2024: 12-24